2023
DOI: 10.1007/s00392-023-02220-5
|View full text |Cite
|
Sign up to set email alerts
|

A simply calculated nutritional index provides clinical implications in patients undergoing transcatheter aortic valve replacement

Abstract: Background Malnutrition is associated with adverse outcomes in patients with aortic stenosis. The Triglycerides × Total Cholesterol × Body Weight Index (TCBI) is a simple scoring model to evaluate the status of nutrition. However, the prognostic relevance of this index in patients undergoing transcatheter aortic valve replacement (TAVR) is unknown. This study aimed to evaluate the association of the TCBI with clinical outcomes in patients undergoing TAVR. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…16 Recent studies indicate that TCBI could serve as a significant prognostic nutrition-related marker in critically ill cardiac patients needing mechanical circulatory support, experiencing acute decompensated heart failure, suffering from acute myocardial infarction, or undergoing transcatheter aortic valve replacement. 17,18,25,26 Figure 3 Association of TCBI with risk of stroke-associated pneumonia. Odds ratios and 95% confidence intervals derived from restricted cubic spline regression, with knots placed at the 5th, 35th, 65th, and 95th percentiles of the distribution of Log TCBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Recent studies indicate that TCBI could serve as a significant prognostic nutrition-related marker in critically ill cardiac patients needing mechanical circulatory support, experiencing acute decompensated heart failure, suffering from acute myocardial infarction, or undergoing transcatheter aortic valve replacement. 17,18,25,26 Figure 3 Association of TCBI with risk of stroke-associated pneumonia. Odds ratios and 95% confidence intervals derived from restricted cubic spline regression, with knots placed at the 5th, 35th, 65th, and 95th percentiles of the distribution of Log TCBI.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Recent studies indicate that TCBI could serve as a significant prognostic nutrition-related marker in critically ill cardiac patients needing mechanical circulatory support, experiencing acute decompensated heart failure, suffering from acute myocardial infarction, or undergoing transcatheter aortic valve replacement. 17 , 18 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 68% of patients were on statins, which was significantly higher in the low-TCBI group. The authors concluded that the association between TCBI and all-cause mortality remained consistent regardless of statin use [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several investigators have reported that malnutrition is a predictor of worse outcomes in patients with severe AS undergoing surgical aortic valve replacement 14,22 . Likewise, Sudo et al have recently shown that patients with low nutritional status were more likely to have right‐sided heart overload and exhibited an increased risk of 3‐year mortality 23 . A recent meta‐analysis indicated that malnutrition was associated with a higher risk of 1‐year all‐cause mortality, and baseline malnutrition, as assessed by objective indices, is associated with worse outcomes after TAVR 24 …”
Section: Discussionmentioning
confidence: 99%
“…14,22 Likewise, Sudo et al have recently shown that patients with low nutritional status were more likely to have right-sided heart overload and exhibited an increased risk of 3-year mortality. 23 A recent meta-analysis indicated that malnutrition was associated with a higher risk of 1-year all-cause mortality, and baseline malnutrition, as assessed by objective indices, is associated with worse outcomes after TAVR. 24 One of the most up-to-date scoring systems for malnutrition is the NPS which consists of serum albumin, total cholesterol level, LMR, and NLR parameters.…”
Section: Discussionmentioning
confidence: 99%